Role of Fine Needle Aspiration Cytology (FNAC) in the Differential Diagnosis of Neck Swelling: A Hospital Based Study - Rahman, Md Hasan Hafijur; Ahmed, Shamsuddin; Razzak, Md Abdur; Stella, Jarin Tasnim; Nahar, Shamsun; Adhikary, Lovely (Journal of Rangpur Medical College, 2026)
Background: Both neck swellings are usually due to lymph nodes, thyroid, paralymphatic, or soft tissue swellings that can vary from inflammatory to malignancies, which are manifestations of head and neck malignancies in adults. FNAC, USG-guided FNAC, and ultrasonography are the major diagnostic modalities in hematologic swellings of lymph nodes that are accurate to the extent of 82–96% sensitivity and in nonthyroid swellings of the neck that are accurate for their sensitivity of 93% and specificity of 72%. This study aims to investigate the cytological distribution of FNAC in 61 cases. Objective: To assess the diagnostic efficacy, accuracy, and cytological findings of Fine Needle Aspiration Cytology (FNAC) in case of neck swellings and correlation of cytological results with demographic details and site-wise distribution for appropriate patient care. Methods: This retrospective study included 61 patients with head and neck swellings from the Department of ENT, Ad-Din Sakina Hospital, between December 2024 and March 2025; FNAC was performed in all cases under strict aseptic conditions using a 23-gauge needle and 10-ml syringe, with aspirated material stained by MGG, H&E, and Papanicolaou methods, Z-N staining applied for suspected tuberculous or purulent cases, and repeat FNAC conducted when initial samples were inadequate. Results: Among 61 FNAC-evaluated neck swellings, thyroid lesions were most common (42.6%), followed by neck and parotid swellings (13.1% each), with female predominance ( 66%) and peak incidence in middle age (45–59 years; 26.2%); cytology showed mainly benign and inflammatory lesions predominantly nodular goiter and lymphadenitis (14.8% each) with fewer malignant cases, highlighting FNAC’s effectiveness in characterizing the anatomical and cytological spectrum. Conclusion: Neck swellings predominantly involve the thyroid gland with female and mid-life predominance, are largely benign with inflammatory and benign neoplastic lesions forming the majority despite a notable malignant proportion, and FNAC proves to be a precise, minimally invasive, and indispensable primary diagnostic tool enabling reliable benign–malignant differentiation and optimal clinical management. J Rang Med Col.2026 Mar;11(1): 208-212